The Effect of Weed Interference, Sowing Date and Method on Phenology, Growth, Protein and Yield of Red Bean (Phaseolus vulgaris L.) - M Edalat; M Kamali (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2017)
To evaluate the effect of weed interference, sowing date and method on phenology, growth, protein and yield of red bean, a split-split plot experiment based on a randomized complete block design with three replications was conducted in the Research Field of College of Agriculture, Shiraz University, Shiraz, Iran during 2013- 2014 growing season. Main plots consisted of planting methods (single-row and double-rows staggered onto the stack), subplots included the presence and absence of weeds, and sowing dates were placed in sub-subplots (15 May, 1 June, and 18 June). Weed competition was effective in reducing 47 percent of LAI, 53.4 percent of dry weight and 47.3 percent of seed yield. Results showed that dry weight of weeds in single-row sowing method was higher than in double-row sowing method. Due to the growing season length in most of the measured traits such as LAI and grain yield, 15 May and 1 June sowing dates were superior compared to the June 28 sowing date. In general, 1st of June sowing date with double-row sowing method could be recommended for Badjgah region.